Assessing the impact of sustainable tourism on Albania’s economy - Banushaj, Aseda; Jorgji, Etis; (Dervishi), Doriana Matraku; Picari, Gentian (Edelweiss Applied Science and Technology, 2025)
Tourism is an option in the Albanian economy since it has a significant impact on employment opportunities and overall economic growth through foreign exchange earnings, among other factors. The research examines the effect of sustainable tourism on Albania’s economy by considering factors such as GDP growth and employment opportunities for businesses and residents. The study employs both data analysis and qualitative feedback from policymakers and community members to derive insights. Findings indicate that tourism contributes to Albania’s economy by supporting GDP growth and serving as a source of employment through direct and indirect opportunities. Additionally, there has been an increase in investment in the tourism sector, particularly in eco-tourism and sustainable hospitality initiatives, emphasizing tourism’s contribution to the economy. The research proposes a series of recommendations to maximize benefits from tourism. Balancing progress with the preservation of the environment and local culture can enhance Albania’s attractiveness to international tourists and promote sustainable socio-economic development. This study underscores the importance of sustainability in shaping the future of Albania’s tourism industry. It provides a foundation for further research on effective approaches and policy recommendations for sustainable tourism development.